Are the Popes Leaving Behind Just War and Embracing JustPeace?. (3rd April 2019) - Hrynkow, Christopher; Power, Maria
Abstract : Since the mid-nineteenth century a significant, though not yet complete, shift in both the politics and the teachings of popes regarding war and peace has occurred, in an increasingly pacifist direction. More specifically, the emphasis of the papal office has noticeably changed from endorsing violence and war toward embracing the essential coupling of peace and justice, holistic peacebuilding, and active nonviolence. Moving beyond the tendency in academic literature to focus solely upon the Catholic Church's teaching on just war, this essay demonstrates how the papacy went through a transformation in their attitudes to war and peace since the accession of Pius IX (r.1846–1878). Mapping developments from the mid-nineteenth century down to the time of this writing in March 2018, this essay demonstrates that while the contemporary popes have left intact certain aspects of the teaching of just war, they nonetheless lend a large measure of support to JustPeace outcomes, defined by the authors as combining peace and social justice in a mutually enhancing and creative tension.